Pengaruh Media Jadwal Pelajaran Terhadap Skor Plak Siswa Sekolah Dasar Samigaluh Kulon Progo - Taadi Taadi; Almujadi Almujadi (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2016)
Oral health education is one way to improve oral health. Counseling must be made interesting, attractive, and without prejudice to the contents. Learning media is anything that can be used to stimulate the mind, feelings of care and skill. The purpose of this study was to determine the effect of timetable media on respondents' plaque scores. This research uses a quasi-experimental design (quasi-experimental) research that aims to determine the effect of timetable media on elementary school students' plaque scores, by analyzing differences in plaque scores of students before and after being given the timetable media. This study uses a quasi experiment with the design of non-Equivalent Control Group, which is a method that is carried out to compare the results of similar intervention controls but do not have to be completely the same. It was done by giving pre-test and post-test in the experimental group and control group. The subjects were elementary school students at grades 3, 4 and 5. The samples were obtained by saturation sampling technique. The treatment of the studies was distributing timetable media which has been conducted plaque score examination (pre-test). The research subjects' plaque score will be examined for the second time (post-test) after 3 months. The data were analyzed by using different test plaque scores before and after treatment. The results showed there was a difference between the mean of knowledge before and after the intervention of 1.2. Statistical tests result showed there was a significant difference at p = 0.001 in confidence level of p = 0.005. There was a difference between the mean score of the plaque before and after the intervention amounted to 30.08 statistical test results showed there was a significant difference at p = 0.001 in confidence level of p = 0.005. In conclusion, there is an effect of timetable media to increase knowledge. There is an influence of timetable media for students to decrease plaque score significantly.